EGAD! There is an ERAD doppelganger in the Golgi - Fonseca, D; Carvalho, P (EMBO Press, 2019)
Disposal of membrane proteins in the late secretory pathway is thought to be exclusively facilitated by ESCRT‐dependent lysosomal degradation. In this issue of The EMBO Journal, Schmidt et al define a previously uncharacterized endosome and Golgi‐associated degradation (EGAD) pathway. This pathway, which has remarkable similarities to ERAD in the endoplasmic reticulum, operates in post‐ER organelles via the proteasome and contributes to lipid homeostasis in eukaryotic cells.